Thermoplastic molding compound

By integrating glass fibers with specific compositions and ethylene copolymers into thermoplastic polyamide compositions, the mechanical properties of molded articles are enhanced, addressing the balance of impact strength, elongation, and stiffness in thermoplastic polyamide materials.

JP7612594B2Active Publication Date: 2025-01-14BASF SE
View PDF 24 Cites 0 Cited by

Patent Information

Application Number
JP2021549241
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-02-20
Filing Date
2020-02-18
Publication Date
2025-01-14
Estimated Expiration
2040-02-18

AI Technical Summary

Technical Problem

Existing thermoplastic polyamide compositions face challenges in achieving a balance of high impact strength, elongation at break, and stiffness, with limited improvements when combined with polyolefin elastomers due to compatibility issues.

Method used

Incorporating glass fibers with specific compositions and properties, such as high tensile strength and elasticity, into thermoplastic polyamide compositions, along with ethylene and C3-12 olefin copolymers grafted with maleic anhydride, to enhance impact strength and elongation at break.

Benefits of technology

The addition of these glass fibers and elastomers significantly increases the impact strength and elongation at break of thermoplastic polyamide compositions, while maintaining high stiffness, resulting in improved mechanical properties of molded articles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612594000001
    Figure 0007612594000001
  • Figure 0007612594000002
    Figure 0007612594000002
  • Figure 0007612594000003
    Figure 0007612594000003
Patent Text Reader

Abstract

A method for increasing the impact strength and / or elongation at break of a molded article made of a molding material containing a thermoplastic polyamide and an elastomer, comprising using glass fiber having a tensile strength according to DIN ISO 527-5 of 86.0 to 92.0 GPa, a tensile modulus of elasticity according to DIN ISO 527-5 of 2600 to 3200 MPa, and a softening point according to DIN ISO 7884-1 of 900°C to 950°C.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the use of certain glass fibers for increasing the impact strength and / or elongation at break of thermoplastic molding materials, including thermoplastic polyamides, and to the corresponding thermoplastic molding materials, methods for producing them, methods of using them, and fibers, films or moldings made from said thermoplastic molding materials. [Background technology]

[0002] It is known to increase the impact strength and / or elongation at break of polyamides by blending them with functional elastomers. The tensile modulus and stress at break may be reduced at the same time.

[0003] US Pat. No. 5,482,997 relates to polyamide compositions containing elastomers with polyamide-reactive groups to increase impact strength. Used in the examples are ethylene-propylene-norbornene terpolymers grafted with maleic anhydride, or thermoplastic polymers based on equal amounts of polypropylene and EPDM rubber, grafted with maleic anhydride.

[0004] US Pat. No. 5,602,200 describes polyamide / polyolefin blends containing unmodified polypropylene or unmodified polyethylene and an ethylene-propylene-diene elastomer optionally grafted with a carboxylic acid or maleic anhydride.

[0005] Blends of polyamides (PA) and polyolefins (POE) show improved properties in terms of hardness and stress / tensile behavior. Because of the limited compatibility of polyamides and polyolefin elastomers, functionalized polyolefin elastomers are often used, e.g. polyolefin elastomers grafted with maleic anhydride. At larger proportions of polyolefin elastomers in the blend, the compatibility cannot be further improved by grafting with maleic anhydride. The reason for this is the limited number of reactive end groups in the polyamide.

[0006] Additionally, the use of special glass fibers in polyamide is advantageous for achieving high stiffness, tear strength, and impact strength.

[0007] EP 2 703 436 A1 describes a polyamide molding material which contains not only particulate fillers but also high-strength glass fibers consisting essentially of silicon dioxide, aluminum oxide and magnesium oxide. Preferred glass fibers contain at least 5% by weight of magnesium oxide and up to 10% by weight of calcium oxide.

[0008] Patent document 4 (EP 3120663 A1) relates to a reinforced polyamide, in particular a long glass fiber reinforced polyamide, which exhibits good mechanical properties and good shrinkage during processing. The polyamide contains special glass fibers composed of 57.5% to 59.5% by weight of SiO2, 17% to 20% by weight of Al2O3, 11 to 13.5% by weight of CaO and 8.5% to 12.5% ​​by weight of MgO. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] US5482997 [Patent Document 2] US5602200 [Patent Document 3] EP2703436A1 [Patent Document 4] EP3120663A1 Summary of the Invention [Problem to be solved by the invention]

[0010] It is an object of the present invention to provide a thermoplastic molding material comprising a thermoplastic polyamide which exhibits increased impact strength and elongation at break in combination with high stiffness and strength.

[0011] A further object of the present invention is to provide an additive which makes it possible to increase the impact strength and / or elongation at break of a molded article made of a thermoplastic molding material comprising a thermoplastic polyamide, said molding material further comprising at least one elastomer. [Means for solving the problem]

[0012] The object of the present invention is to provide a glass fiber, preferably a glass fiber having a tensile strength according to DIN ISO 527-5 of 86.0 to 92.0 GPa, a tensile modulus according to DIN ISO 527-5 of 2600 to 3200 MPa, and a softening point according to DIN ISO 7884-1 of 900° C. to 950° C. C1) 55.5% to 62.0% by mass of SiO2; C2) 14.0 mass% to 18.0 mass% Al2O3, C3) 11.0% by mass to 16.0% by mass of CaO, C4) 6.0% by mass to 10.0% by mass of MgO; C5) 0% by mass to 4.0% by mass of further oxides; wherein the total percentage of C3) CaO and C4) MgO is in the range of 17.0 to 24.0 mass%, and the total percentage of C1) to C5) is 100 mass%, is used to increase the impact strength and / or breaking elongation of a molded article made of a molding material containing a thermoplastic polyamide and an elastomer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Standards indicate standards that came into effect in 2019.

[0014] In this case, the thermoplastic molding material is preferably b1) As component B1), ethylene and C 3~12 -Olefin, C 1~12 - copolymers with at least one comonomer selected from alkyl (meth)acrylates, (meth)acrylic acid and maleic anhydride, b2) as component B2), polyethylene or polypropylene; At least one elastomer selected from Components B1) and B2) may additionally be grafted with maleic anhydride.

[0015] The above-mentioned objectives are a) 30.0% to 89.0% by weight of at least one thermoplastic polyamide as component A), b) 1.0% to 30.0% by weight of at least one elastomer as component B), b1) As component B1), ethylene and C 3~12 -Olefin, C 1~12 - copolymers with at least one comonomer selected from alkyl (meth)acrylates, (meth)acrylic acid and maleic anhydride, b2) as component B2), polyethylene or polypropylene; at least one elastomer, components B1) and B2) being optionally grafted with maleic anhydride; c) as component C), 10.0% by mass to 69.0% by mass of glass fibers, which have a tensile strength according to DIN ISO 527-5 of 86.0 to 92.0 GPa, a tensile modulus according to DIN ISO 527-5 of 2600 to 3200 MPa, and a softening point according to DIN ISO 7884-1 of 900 ° C. to 950 ° C.; d) 0% to 30.0% by weight of further additives and processing aids as component D); The above-mentioned object is also achieved by a thermoplastic molding material which comprises: a) 30.0% to 89.0% by weight of at least one thermoplastic polyamide as component A), b) 1.0% to 30.0% by weight of at least one elastomer as component B), b1) As component B1), ethylene and C 3~12 -Olefin, C 1~12 - copolymers with at least one comonomer selected from alkyl (meth)acrylates, (meth)acrylic acid and maleic anhydride, b2) as component B2), polyethylene or polypropylene; at least one elastomer, components B1) and B2) being optionally grafted with maleic anhydride; c) 10.0% by weight to 69.0% by weight of glass fiber as component C), C1) 55.5% to 62.0% by mass of SiO2; C2) 14.0 mass% to 18.0 mass% Al2O3, C3) 11.0% by mass to 16.0% by mass of CaO, C4) 6.0% by mass to 10.0% by mass of MgO; C5) 0% by mass to 4.0% by mass of further oxides; A glass fiber having a composition represented by the formula: wherein the total percentage of C3) CaO and C4) MgO is in the range of 17.0 to 24.0 mass%, and the total percentage of C1) to C5) is 100 mass%. d) 0% to 30.0% by weight of further additives and processing aids as component D); and the total percentage of components A) to D) is 100% by weight.

[0016] This object is further achieved by a process for producing such a thermoplastic molding material by mixing components A) to C) and optionally D).

[0017] This object is further achieved by the use of the thermoplastic molding materials, by the production of fibers, films and moldings, by the corresponding fibers, films and moldings and by the process for their production.

[0018] According to the invention, it has been found that the use of specific glass fibres of the above-mentioned composition increases the impact strength and / or elongation at break of polyamide moulding materials, in particular polyamide / elastomer blends.

[0019] This effect is not limited to polyamides, b1) As component B1), ethylene and C 3~12 -Olefin, C 1~12 - copolymers with at least one comonomer selected from alkyl (meth)acrylates, (meth)acrylic acid and maleic anhydride, b2) as component B2), polyethylene or polypropylene; and components B1) and B2) have been observed in moldings composed of thermoplastic molding materials which may additionally be grafted with maleic anhydride.

[0020] The components of the thermoplastic molding material according to the invention are explained in more detail below.

[0021] Component A) As component A), the thermoplastic molding material comprises 30.0% by weight to 89.0% by weight, preferably 43.0% by weight to 78.0% by weight, preferably 52.0% by weight to 72.0% by weight and in particular 56.5% by weight to 66.5% by weight of at least one thermoplastic polyamide. The polyamide of the molding material according to the invention usually has a viscosity number of 90 to 210 ml / g, preferably 110 to 160 ml / g, measured according to ISO 307 at 25° C. in a 0.5% by weight solution in 96.0% by weight sulfuric acid.

[0022] Semicrystalline or amorphous resins having a molecular weight (weight average) of at least 5000, such as those described in U.S. Patents 2,071,250, 2,071,251, 2,130,523, 2,130,948, 2,241,322, 2,312,966, 2,512,606, and 3,393,210, are preferred.

[0023] Examples of these are polyamides which are derived from lactams having 7 to 13 ring members, such as polycaprolactam, polycaprylolactam, and polylaurolactam, and polyamides which can be obtained by reaction of dicarboxylic acids with diamines.

[0024] Dicarboxylic acids which can be used include alkane dicarboxylic acids having 6 to 12 carbon atoms, in particular 6 to 10 carbon atoms, and aromatic dicarboxylic acids. These include only the acids adipic acid, azelaic acid, sebacic acid, dodecanedioic acid and terephthalic and / or isophthalic acid.

[0025] Particularly suitable diamines include alkanediamines having 6 to 12, especially 6 to 9, carbon atoms, and m-xylylenediamine, di(4-aminophenyl)methane, di(4-aminocyclohexyl)methane, 2,2-di(4-aminophenyl)propane, 2,2-di(4-aminocyclohexyl)propane, or 1,5-diamino-2-methylpentane.

[0026] Preferred polyamides are polyhexamethylene adipamide, polyhexamethylene sebacamide, polycaprolactam and copolyamide 6 / 66, especially those having from 5% to 95.0% by weight of caprolactam units.

[0027] Suitable polyamides further include those which are obtainable by so-called direct polymerization in water from ω-aminoalkylnitriles, such as aminocapronitrile (PA6) and adipodinitrile and hexamethylenediamine (PA 66), as described, for example, in DE-A-10313681, EP-A-1198491 and EP922065.

[0028] Also suitable are polyamides, for example obtainable by condensation of 1,4-diaminobutane with adipic acid at elevated temperature (polyamide 4,6). Methods for the preparation of polyamides having this structure are described, for example, in EP-A-38094, EP-A-38582 and EP-A-039524.

[0029] Also suitable are polyamides obtained by copolymerization of two or more of the abovementioned monomers, or mixtures of several polyamides in any desired proportions.

[0030] Suitable polyamides preferably have a melting point below 265°C.

[0031] The following non-exhaustive list includes the polyamides mentioned above and further polyamides within the meaning of the present application and monomers present.

[0032] AB Polymer: PA4 Pyrrolidone PA6 ε-caprolactam PA7 Ethanolactam PA8 Caprolactam PA9 9-Aminopelargonic acid PA11 11-aminoundecanoic acid PA12 Laurolactam AA / BB polymer: PA46 Tetramethylenediamine, adipic acid PA66 Hexamethylenediamine, Adipic acid PA69 Hexamethylenediamine, Azelaic acid PA610 Hexamethylenediamine, Sebacic acid PA612 Hexamethylenediamine, Decanedicarboxylic acid PA613 Hexamethylenediamine, undecanedicarboxylic acid PA1212 1,12-Dodecanediamine, decanedicarboxylic acid PA1313 1,13-Diaminotridecane, undecanedicarboxylic acid PA6T Hexamethylenediamine, Terephthalic acid PAMXD6 m-Xylylenediamine, adipic acid PA9T Nonamethylenediamine, Terephthalic acid AA / BB polymer: PA6I Hexamethylenediamine, Isophthalic acid PA6-3-T Trimethylhexamethylenediamine, terephthalic acid PA6 / 6T (PA6 and PA6T, see below) PA6 / 66 (see PA6 and PA66) PA6 / 12 (PA6 and PA12, see below) PA66 / 6 / 610 (see PA66, PA6 and PA610) PA6I / 6T (PA6I and PA6T, see below) PAPACM12 Diaminodicyclohexylmethane, laurolactam PA6I / 6T / PACMT PA6I / 6T + diaminodicyclohexylmethane, terephthalic acid PA6T / 6I / MACMT PA6I / 6T + Dimethyldiaminocyclohexylmethane, Terephthalic acid PA6T / 6I / MXDT PA6I / 6T+m+Xylylenediamine, Terephthalic acid PA12 / MACMI Laurolactam, Dimethyldiaminodicyclohexylmethane, Isophthalic Acid PA12 / MACMT Laurolactam, Dimethyldiaminodicyclohexylmethane, Terephthalic Acid PAPDA-T Phenylenediamine, Terephthalic Acid PA6T / 6I (PA6T and PA6I, see) PA6T / 66 (see PA6T and PA66)

[0033] Component A) may be a blend of at least one aliphatic polyamide and at least one semi-aromatic or aromatic polyamide.

[0034] The component A) used according to the invention is, for example, a mixture comprising polyamide 6 and polyamide 6.6 and optionally polyamide 6I / 6T. It is preferable to use polyamide 6.6 in the majority. The amount of polyamide 6 is preferably 5.0% to 50.0% by weight, particularly preferably 10.0% to 30.0% by weight, based on the amount of polyamide 6.6. If polyamide 6I / 6T is used jointly, its proportion is preferably 10.0% to 25.0% by weight, particularly preferably 0% to 25.0% by weight, based on the amount of polyamide 6.6.

[0035] Instead of or in addition to polyamide 6I / 6T, it is also possible to use polyamide 6I or polyamide 6T or mixtures thereof.

[0036] Of particular use according to the invention are polyamide 6, polyamide 66 and their copolymers or mixtures. Polyamide 6 or polyamide 66 preferably have a viscosity number in the range of 80 to 180 ml / g, in particular 85 to 160 ml / g, in particular 90 to 140 ml / g, measured in a 0.5% by weight solution in 96.0% by weight sulfuric acid at 25° C. according to ISO 307.

[0037] Suitable polyamide 66 preferably has a viscosity number in the range from 110 to 170 ml / g, particularly preferably from 130 to 160 ml / g.

[0038] For suitable semi-crystalline and amorphous polyamides, further reference may be made to DE 102005049297. These have a viscosity number of 90 to 210 ml / g, preferably 110 to 160 ml / g, measured in a 0.5% by weight solution in 96% by weight sulfuric acid at 25° C. according to ISO 307.

[0039] In polyamide 6 or polyamide 66, 0% by mass to 10% by mass, preferably 0% by mass to 5% by mass, may be replaced by a semi-aromatic polyamide. It is particularly preferred that no semi-aromatic polyamide is co-used.

[0040] Component B) As component B), the thermoplastic molding material comprises 1.0% by weight to 30.0% by weight, preferably 2.0% by weight to 20.0% by weight, particularly preferably 3.0% by weight to 10.0% by weight and in particular 3.5% by weight to 7.0% by weight of at least one elastomer.

[0041] Component B), the elastomer, is preferably b1) As component B1), ethylene and C 3~12 -Olefin, C 1~12 - copolymers with at least one comonomer selected from alkyl (meth)acrylates, (meth)acrylic acid, maleic anhydride, b2) as component B2), polyethylene or polypropylene; where components B1) and B2) may additionally be grafted with maleic anhydride.

[0042] Component B1) may contain one or more different comonomers, preferably 1 to 3 different copolymers, particularly preferably 1 or 2 different comonomers. 3~12 The olefin is preferably a terminal, linear C 3~12 -olefins, particularly preferably C 3~8 -olefins. Examples of suitable olefins are propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene and 1-octene.

[0043] C 1~12 -Alkyl (meth)acrylate is C 1~12 -Alkyl radical, preferably C 2~6 -Alkyl radicals, including, for example, methyl, ethyl, propyl, butyl, pentyl, hexyl, ethylhexyl radicals. Alkyl acrylates are preferably involved.

[0044] In the copolymers of component B1), the proportion of ethylene-based units is from 1% to 99% by weight, particularly preferably from 60% to 98% by weight and very particularly preferably from 84% to 96% by weight.

[0045] The following preferred amounts apply to the comonomers: C 3~12 Olefins: preferably 99% by mass to 1% by mass, particularly preferably 40% by mass to 10% by mass, C 1~12 -Alkyl (meth)acrylate: preferably 40% by mass to 2% by mass, particularly preferably 30% by mass to 5% by mass, (Meth)acrylic acid: preferably 40% by mass to 2% by mass, particularly preferably 30% by mass to 5% by mass, Maleic anhydride: preferably 3% by mass to 0.01% by mass, particularly preferably 2% by mass to 0.1% by mass.

[0046] The total amount of comonomers is preferably in the range of 1% by mass to 99% by mass, particularly preferably in the range of 2% by mass to 40% by mass.

[0047] The copolymers of component B1) may be random or block copolymers. The former consist of a crystallized and therefore physically crosslinked main polymer (polyethylene), the crystallinity of which is reduced by randomly inserted comonomers along the chain, so that the crystallites in the finished molding material are no longer in direct contact. They therefore act as isolated crosslinking points, as in conventional elastomers.

[0048] In block copolymers, the hard and soft segments in the molecule are highly separated. For thermoplastic elastomers, below a certain temperature, the material breaks down into a continuous phase and a discontinuous phase. If the latter drops below its glass temperature, it immediately acts again as a crosslinking point.

[0049] The copolymers of component B1) may additionally be grafted with maleic anhydride. The maleic anhydride used for grafting is preferably used in an amount of 5% by weight to 0.005% by weight, particularly preferably 3% by weight to 0.01% by weight, based on the copolymer of component B1). In the grafted copolymers of component B1), the proportion of maleic anhydride is preferably in the range of 2% by weight to 0.1% by weight, based on the ungrafted copolymer of component B1).

[0050] Component B1) has a melt flow index (MVR) (190°C / 2.16kg, according to ISO1133) of preferably 0.1 to 20 cm 3 / 10 min, and preferably 0.1 to 15 cm 3 / 10 minutes.

[0051] Alternatively or additionally to component B1), it is possible to use polyethylene or polypropylene or a mixture of both as component B2), which may additionally be grafted with maleic anhydride, the proportion of maleic anhydride being between 5% and 0.005% by weight, particularly preferably between 2% and 0.1% by weight, based on the polyolefin.

[0052] Component B2) preferably has an MVR (190°C / 2.16kg according to ISO 1133) value of preferably 0.1 to 20cm 3 / 10 min, and preferably 0.1 to 15 cm 3 / 10 minutes.

[0053] The term "elastomer" refers to components B1) and B2), which may optionally be grafted with maleic anhydride. This can preferably be a thermoplastic elastomer (TPE). At room temperature, TPEs behave in a manner that corresponds to classical elastomers, but when heated, they are plastically deformable and therefore exhibit thermoplastic behavior.

[0054] Also usable in accordance with the invention are mixtures of components B1) and B2). These are in particular elastomeric alloys (polyblends).

[0055] Thermoplastic elastomers are usually copolymers that contain a "soft" elastomeric component and a "hard" thermoplastic component. Their properties are therefore somewhere between those of elastomers and thermoplastics.

[0056] Polyolefin elastomers (POE), for example, are polymerized using metallocene catalysts and examples include ethylene-propylene elastomers (EPR or EPDM).

[0057] The most common polyolefin elastomers are copolymers of ethylene and butene or ethylene and octene.

[0058] For a further description of elastomers suitable as component B), reference may be made to US Pat. No. 5,482,997, US Pat. No. 5,602,200, US Pat. No. 4,174,358 and WO 2005 / 014278 A1.

[0059] Suitable elastomers are, for example, those available from Lyondellbasell under the trade names Lucalen A2540D and Lucalen A2700M. Lucalen A2540D is a low density polyethylene with n-butyl acrylate comonomer. It has a viscosity of 0.923 g / cm 3 and a Vicat softening temperature of 85° C. with a butyl acrylate content of 6.5% by weight.

[0060] Lucalen A2700M is also a low density polyethylene with butyl acrylate comonomer. It has a density of 0.924 g / cm 3 It has a density of 1000, a Vicat softening temperature of 60°C, and a melting temperature of 95°C.

[0061] The polymer resin Exxelor™ VA1801 from ExxonMobil is a semi-crystalline ethylene copolymer functionalized with maleic anhydride by reactive extrusion and has a medium viscosity. The first polymer backbone is fully saturated. The density is 0.880 g / cm 3 and the proportion of maleic anhydride is typically in the range of 0.5% to 1.0% by mass.

[0062] Further suitable components B) are known to those skilled in the art.

[0063] Component C) As component C), the molding material according to the invention comprises 10.0% to 69.0% by weight, preferably 0.0% to 55.0% by weight, and in particular 25.0% to 45.0% by weight, in particular 30.0% to 40.0% by weight, of glass fibers having a tensile strength according to DIN ISO 527-5 of 86.0 to 92.0 GPa, a tensile modulus of elasticity according to DIN ISO 527-5 of 2600 to 3200 MPa, and a softening point according to DIN ISO 7884-1 of 900 ° C. to 950 ° C., said glass fibers being preferably C1) 55.5% to 62.0% by mass of SiO2; C2) 14.0 mass% to 18.0 mass% Al2O3, C3) 11.0% by mass to 16.0% by mass of CaO, C4) 6.0% by mass to 10.0% by mass of MgO; C5) 0% by mass to 4.0% by mass of further oxides; and the total percentage of C1) to C5) is 100 mass %. Further oxides C5) are understood to mean the oxides of the elements Li, Zn, Mn, Le, V, Ti, Be, Sn, Ba, Zr, Sr, Fe, B, Na, K or mixtures thereof.

[0064] For example, the glass fibres may contain up to 1% by weight Li2O and / or TiO2, preferably up to 0.5% by weight.

[0065] If present, Fe2O3 and / or B2O3 may be included in an amount of 0.1 to 3% by mass, preferably 0.2 to 3% by mass.

[0066] According to the present invention, if present, the oxides of the elements Zn, Mn, Le, V, Be, Sn, Ba, Zr, and Sn may each be present in an amount of 0.05 to 3% by mass, preferably 0.2% to 1.5% by mass.

[0067] The appropriate amount of Na2O and / or K2O, if present, is at least 0.2% by mass, preferably 0.3% to 4% by mass.

[0068] An essentially preferred aspect of the glass fiber composition according to the present invention is a) The ratio of MgO(C4)):Al2O3(C2)) is preferably at least 1.4 to 3.0 or less, particularly 1.5 to 2.8, b) The ratio of MgO(C4)):CaO(C3)) is preferably 1.4 to 2.7, particularly 1.2 to 2.6.

[0069] The total of MgO + CaO and MgO + Al2O3 is particularly preferably limited to the following ranges: a) 17.0% by mass < MgO + CaO < 24.0% by mass, particularly 18.0% by mass < MgO + CaO < 23.0% by mass, and b) 20.0% by mass < MgO + Al2O3 < 26.0% by mass, particularly 21.0% by mass < MgO + Al2O3 < 25.0% by mass.

[0070] The production of glass fiber C) is in the usual form and is disclosed in WO2013 / 156477 and EP3130633A1. For further details, this literature is referred to.

[0071] The glass fiber is preferably used as chopped glass according to the present invention, and the chopped glass has a diameter of 6 to 20 μm, preferably 8 to 12 μm, particularly 10 μm, where the cross-section of the glass fiber may be not only circular but also oval or angular.

[0072] The glass fibers C) may be surface-treated with a silane compound for better compatibility with thermoplastics. Suitable silane compounds have the general formula (X-(CH2) n ) k -Si-(OC m H 2m+1 ) 4-k where the substitutents in the formula are defined as follows: X: NH2-, HO-, [ka] n: an integer of 2 to 10, preferably 3 to 4; m: an integer of 1 to 5, preferably 1 to 2; k: an integer of 1 to 3, preferably 1.

[0073] Preferred silane compounds are aminopropyltrimethoxysilane, aminobutyltrimethoxysilane, aminopropyltriethoxysilane, aminobutyltriethoxysilane and the corresponding silanes which contain a glycidyl group as the substituent X.

[0074] The silane compounds are usually used for the surface coating in an amount of 0.01% to 2% by weight, preferably 0.025% to 1.0% by weight, and in particular 0.05% to 0.5% by weight (based on (C)).

[0075] Other suitable coating compositions (also known as sizes) are based on isocyanates, phenolic resins, or acrylic derivatives.

[0076] Component D) As component D), the composition according to the invention comprises from 0% to 30.0% by weight, preferably from 0% to 20.0% by weight, in particular from 0% to 10.0% by weight and especially from 0% to 5.0% by weight of further additives. If such additives are jointly used, the minimum amount is 0.1% by weight, preferably 0.5% by weight and in particular 0.8% by weight.

[0077] If component D) is used in combination, the upper limit for component A) is correspondingly reduced. Thus, for example, in the case of a minimum amount of 0.1% by weight of component D), the upper limit for component A) is 88.9% by weight.

[0078] Further additives contemplated include glass fibers different from component C), fillers and reinforcing agents different from the glass fibers, thermoplastic polymers different from components A) and B), or other additives.

[0079] As component D), the thermoplastic molding material may contain 0% to 20% by weight, preferably 0% to 10% by weight, particularly preferably 0% to 5% by weight, of glass fibers different from component C).

[0080] In particular, those used as component D) are chopped glass fibers. Component D) in particular comprises glass fibers, whereby short fibers are preferably used. These preferably have a length of 2 to 50 mm and a diameter of 5 to 40 μm. Alternatively, it is possible to use continuous fibers (rovings). Suitable fibers include those with circular and / or non-circular cross sections, in the latter case the ratio of the main cross-sectional axis to the secondary cross-sectional axis is in particular >2, preferably in the range from 2 to 8 and particularly preferably 3 to 5.

[0081] In a particular embodiment, component D) comprises so-called "flat glass fibres". These in particular have an oval or elliptical cross-sectional shape, or a necked elliptical (so-called "cocoon" fibres), a rectangular or substantially rectangular cross-sectional shape. Preferably, glass fibres are used which have a non-circular cross-section and a dimensional ratio of the main cross-sectional axis to the secondary cross-sectional axis of more than 2, preferably between 2 and 8, in particular between 3 and 5.

[0082] The reinforcement of the molding material according to the invention may be carried out using a mixture of glass fibres with circular and non-circular cross-sectional shapes, in a particular embodiment the proportion of flat glass fibres as defined above predominates, i.e. it is more than 50% of the total fibre mass.

[0083] If glass fibre rovings are used as component D), the fibres preferably have a diameter of 10 to 20 μm, preferably 12 to 18 μm. The cross section of these glass fibres may be circular, oval, elliptical, substantially rectangular or oblong. Particular preference is given to so-called flat glass fibres, with a ratio of the cross-sectional axes between 2 and 5. E-glass fibres are in particular used. However, it is also possible to use any other glass fibre, for example A, C, D, M, S or R glass fibres, or any mixtures of these, or mixtures with E-glass fibres.

[0084] In the present invention, "fillers and reinforcing materials" (=possible component D) should be interpreted broadly and include particulate fillers, fibrous materials different from glass fibers, and any intermediate forms. Particulate fillers may have a wide range of particle sizes, ranging from dust-like to large particles. Possible filler materials include organic or inorganic fillers and reinforcing materials. Usable here are, for example, inorganic fillers such as kaolin, chalk, wollastonite, talc, calcium carbonate, silicates, titanium dioxide, zinc oxide, graphite, glass particles such as glass spheres, nanoscale fillers such as carbon nanotubes, nanoscale sheet silicates, nanoscale alumina (Al2O3), nanoscale titanium dioxide (TiO2), graphene, permanent magnets, or magnetizable metal compounds and / or alloys, phyllosilicates, and nanoscale silicon dioxide (SiO2). The fillers may be surface-treated.

[0085] Examples of phyllosilicates that can be used in the molding material according to the invention include kaolin, serpentine, talc, mica, vermiculite, illite, smectite, montmorillonite, hectorite, double hydroxides, or mixtures thereof. The phyllosilicates may be surface-treated or untreated.

[0086] One or more fibrous materials may also be used, preferably selected from known inorganic reinforcing fibers, such as boron fibers, carbon fibers, silica fibers, ceramic fibers, and basalt fibers; organic reinforcing fibers, such as aramid fibers, polyester fibers, nylon fibers, polyethylene fibers, and natural fibers, such as wood fibers, flax fibers, hemp fibers, and sisal fibers.

[0087] It is particularly preferable to use carbon fibers, aramid fibers, boron fibers, metal fibers or potassium titanate fibers.

[0088] It is preferred that no glass fibres different from component C) are used and that no other fibres and reinforcing materials are used.

[0089] The thermoplastic polymer different from components A) and B) is preferably -C2-C 10 -monoolefins such as ethylene or propylene, 1,3-butadiene, 2-chloro-1,3-butadiene, vinyl alcohol, and their C2-C 10 - alkyl esters, vinyl chloride, vinylidene chloride, vinylidene fluoride, tetrafluoroethylene, glycidyl acrylate, glycidyl methacrylate, acrylates and methacrylates, branched or unbranched C1-C 10 - those with alcohols, vinyl aromatics, such as homo- or copolymers containing, in copolymerized form, at least one monomer selected from styrene, acrylonitrile, methacrylonitrile, α,β-ethylenically unsaturated mono- and dicarboxylic acids, and maleic anhydride; - vinyl acetal homo- and copolymers, polyvinyl ester, -Polycarbonate (PC), Polyesters, such as polyalkylene terephthalates, polyhydroxyalkanoates (PHAs), polybutylene succinates (PBSs), polybutylene succinate adipates (PBSAs), Polyether, Polyetherketone, -Thermoplastic polyurethane (TPU), -polysulfides, Polysulfone, Polyethersulfone, cellulose alkyl esters, and mixtures thereof.

[0090] Examples are polyacrylates with identical or different radicals from C4-C8 alcohols, in particular butanol, hexanol, octanol and 2-ethylhexanol, polymethyl methacrylate (PMMA), methyl methacrylate-butyl acrylate copolymers, acrylonitrile-butadiene-styrene copolymers (ABS), ethylene-propylene copolymers, ethylene-propylene-diene copolymers (EPDM), polystyrene (PS), styrene-acrylonitrile copolymers (SAN), acrylonitrile copolymers (ACN), polyvinyl chloride (PCC ... Examples of suitable cellulose acetate copolymers include styrene-styrene-acrylate (ASA), styrene-butadiene-methyl methacrylate copolymer (SBMMA), styrene-maleic anhydride copolymer, styrene-maleic acid copolymer (SMA), polyoxymethylene (POM), polyvinyl alcohol (PVAL), polyvinyl acetate (PVA), polyvinyl butyral (PVB), polycaprolactone (PCL), ethylene cellulose (EC), cellulose acetate (CA), cellulose propionate (CP) or cellulose acetate / butyrate (CAB).

[0091] The at least one thermoplastic polymer optionally present in the molding material according to the invention is preferably polyvinyl chloride (PVC), polyvinyl butyral (PVB), homo- and copolymers of vinyl acetate, homo- and copolymers of styrene, polyacrylates, thermoplastic polyurethanes (TPUs) or polysulfides.

[0092] Suitable preferred additives D) are lubricants and heat stabilizers, but also flame retardants, light stabilizers (UV stabilizers, UV absorbers or UV blockers), dyes and nucleating agents and optionally metal pigments, metal flakes, metal coated particles, antistatic agents, conductive additives, mold release agents, optical brighteners, defoamers, etc.

[0093] As component D), the molding material according to the invention may comprise preferably 0.01% to 3% by weight, particularly preferably 0.02% to 2% by weight and in particular 0.05% to 1.0% by weight of at least one heat stabilizer, based on the total weight of the composition.

[0094] The heat stabilizer is preferably selected from copper compounds, secondary aromatic amines, sterically hindered phenols, phosphites, phosphonites and mixtures thereof.

[0095] When a copper compound is used, the amount of copper is preferably 0.003% to 0.5% by weight, in particular 0.005% to 0.3% by weight, and particularly preferably 0.01% to 0.2% by weight, based on the total weight of the composition.

[0096] If stabilizers based on secondary aromatic amines are used, the amount of these stabilizers is preferably 0.2% to 2% by weight, particularly preferably 0.2% to 1.5% by weight, relative to the total weight of the composition.

[0097] If stabilizers based on sterically hindered phenols are used, the amount of these stabilizers is preferably from 0.1% to 1.5% by weight, particularly preferably from 0.2% to 1% by weight, relative to the total weight of the composition. If stabilizers based on phosphites and / or phosphonites are used, the amount of these stabilizers is preferably from 0.1% to 1.5% by weight, particularly preferably from 0.2% to 1% by weight, relative to the total weight of the composition.

[0098] Suitable compounds D) of monovalent or divalent copper are, for example, salts of monovalent or divalent copper with inorganic or organic acids or monovalent or divalent phenols, oxides of monovalent or divalent copper or complexes of copper with ammonia, amines, amides, lactams, cyanides or phosphines, preferably Cu(I) or Cu(II) salts of hydrohalic or hydrocyanic acids or copper salts of aliphatic carboxylic acids. Particularly preferred are the monovalent copper compounds CuCl, CuBr, Cul, CuCN and Cu2O and the divalent copper compounds CuCl2, CuSO4, CuO, copper(II) acetate or copper(II) stearate.

[0099] The copper compounds are commercially available and / or their preparation is known to those skilled in the art. The copper compounds may be used as such or in the form of concentrates. Concentrates should be understood as meaning polymers, preferably of the same chemical nature as component A), which contain copper salts in high concentrations. The use of concentrates is a common process and is often used, preferably when very small amounts of input materials are added. It is advantageous to use the copper compounds in combination with further metal halides, in particular alkali metal halides, such as NaI, KI, NaBr, KBr, where the molar ratio of metal halide to copper halide is 0.5-20, preferably 1-10, particularly preferably 3-7.

[0100] Particularly preferred examples of stabilizers based on secondary aromatic amines and useful according to the present invention include an adduct of phenylenediamine with acetone (Naugard® A), an adduct of phenylenediamine with linoleic acid, 4,4'-bis(α,α-dimethylbenzyl)diphenylamine (Naugard® 445), N,N'-dinaphthyl-p-phenylenediamine, N-phenyl-N'-cyclohexyl-p-phenylenediamine or a mixture of two or more thereof.

[0101] Preferred examples of stabilizers which can be used according to the invention and which are based on sterically hindered phenols include N,N'-hexamethylenebis-3-(3,5-di-tert-4-hydroxyphenyl)propionamide, bis(3,3-bis(4'-hydroxy-3'-tert-butylphenyl)butanoic acid) glycol ester, 2,1'-thioethylbis(3-(3,5-di-tert-butyl-4-hydrophenyl))propionate, 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), triethylene glycol 3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propionate or mixtures of two or more of these stabilizers.

[0102] Preferred phosphites and phosphonites are triphenyl phosphite, diphenyl alkyl phosphite, phenyl dialkyl phosphite, tris(nonylphenyl) phosphite, trilauryl phosphite, trioctadecyl phosphite, distearyl pentaerythrityl diphosphite, tris(2,4-di-tert-butylphenyl) phosphite, diisodecyl pentaerythrityl diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythrityl diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythrityl diphosphite, diisodecyloxy pentaerythrityl diphosphite, bis(2,4-di-tert-butyl-6-methylphenyl) pentaerythrityl diphosphite, bis(2,4,6-tris(tert-butylphenyl) pentaerythrityl diphosphite, tristearyl sorbitol triphosphate, tris(2,4-di-tert-butylphenyl) pentaerythrityl diphosphite, tris(2,4,6-tris( ...2,4,6-tris(2,4,6-tris(2,4,6-tris(2,4,6-tris(2,4,6-tris(2,4,6-tri phosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'biphenylenediphosphonate, 6-isooctyloxy-2,4,8,10-tetra-tert-butyl-12H-dibenzo-[d,g]-1,3,2-dioxaphosphocin, 6-fluoro-2,4,8,10-tetra-tert-butyl-12-methyldibenzo-[d,g]-1,3,2-dioxaphosphocin, bis(2,4-di-tert-butyl-6-methylfuran Preferred are tris[2-tert-butyl-4-thio(2'-methyl-4'-hydroxy-5'-tert-butyl)phenyl-5-methylphenyl phosphite and tris(2,4-tert-butylphenyl)phosphite (Hostanox® PAR24: commercially available from BASFSE).

[0103] A preferred embodiment of the heat stabilizer is composed of a combination of an organic heat stabilizer (especially Hostanox PAR 24 and Irganox 1010), a bisphenol A-based epoxide (especially Epikote 1001) and a copper stabilizer based on CuI and KI. An example of a commercially available stabilizer mixture consisting of an organic stabilizer and an epoxide is Irgatec® NC66 from BASF SE. Heat stabilizers based exclusively on Cu and Kl are particularly preferred. In addition to copper or copper compounds, the use of other transition metal compounds, in particular metal salts or metal oxides of groups VB, VIB, VIIB or VIIIB of the periodic table, is possible or otherwise excluded. It may or may not be further preferred to not add transition metals of groups VB, VIB, VIIB or VIIIB of the periodic table, such as iron or steel powder, to the molding material according to the invention.

[0104] The molding material according to the invention may contain as additive E) 0% to 20.0% by weight, particularly preferably 0% to 10.0% by weight, of at least one flame retardant, based on the total weight of the composition. If the molding material according to the invention contains at least one flame retardant, these are preferably contained in an amount of 0.01% to 20% by weight, particularly preferably 0.1% to 10% by weight, based on the total weight of the composition. Suitable flame retardants include halogen-containing and halogen-free flame retardants and their synergists (see Gaechter / Mueller, 3rd edition, 1989, Hanser Verlag, chapter 11). Preferred halogen-free flame retardants are red phosphorus, phosphinic or diphosphinic salts, and / or nitrogen-containing flame retardants, such as melamine, melamine cyanurate, melamine sulfate, melamine borate, melamine oxalate, melamine phosphate (primary, secondary) or secondary melamine pyrophosphate, melamine neopentyl glycol borate, guanidine and their derivatives known to those skilled in the art and polymeric melamine phosphates (CAS Nos.: 56386-64-2 and 218768-84-4 and also EP-A-1095030), ammonium polyphosphate, trishydroxyethyl isocyanate (optionally ammonium polyphosphate in a mixture with trishydroethyl isocyanurate) (EP-A-0584567). Further N- or P-containing flame retardants or PN condensates suitable as flame retardants and customary synergists therefor, such as oxides or borates, may be found in DE-A-102004049342. Suitable halogen-containing flame retardants are, for example, oligomeric brominated polycarbonates (BD 52 Great Lakes) or polypentabromobenzyl acrylates with N greater than 4 (FR1025 Dead sea bromine), reaction products of tetrabromobisphenol A with epoxides, brominated oligomeric or polymeric styrenes, dechlorane, which is usually used together with antimony oxide as synergist (for further details and further flame retardants, reference is made to DE-A-102004050025).

[0105] The thermoplastic molding material according to the invention may contain from 0% to 1.5% by weight, preferably from 0.05% to 1.5% by weight and particularly preferably from 0.1% to 1% by weight of a lubricant.

[0106] Preferred are Al salts, alkali metal salts, alkaline earth metal salts or esters or amides of fatty acids having 10 to 44 carbon atoms, preferably 14 to 44 carbon atoms. The metal ions are preferably alkaline earth metals and Al, particularly preferably Ca or Mg. Preferred metal salts are Ca stearate and Ca montanate and Al stearate. It is also possible to use mixtures of different salts in any desired mixing ratio.

[0107] The carboxylic acids may be monobasic or dibasic. Examples include pelargonic acid, palmitic acid, lauric acid, margaric acid, dodecanedioic acid, behenic acid, and particularly preferred are stearic acid, capric acid, and montanic acid (a mixture of fatty acids having 30 to 40 carbon atoms).

[0108] The fatty acid alcohol may be monohydric to tetrahydric. Examples of the alcohol include n-butanol, n-octanol, stearyl alcohol, ethylene glycol, propylene glycol, neopentyl glycol, and pentaerythritol, with glycerol and pentaerythritol being preferred.

[0109] The aliphatic amine may be monofunctional to trifunctional. Examples thereof are stearylamine, ethylenediamine, propylenediamine, hexamethylenediamine, and di(6-aminohexyl)amine, with ethylenediamine and hexamethylenediamine being particularly preferred. Preferred esters or amides are correspondingly glyceryl distearate, glyceryl tristearate, ethylenediamine distearate, glyceryl monopalmitate, glyceryl trilaurate, glyceryl monobehenate, and pentaerythritol tetrastearate.

[0110] It is also possible to use mixtures of different esters or amides or esters in combination with amides in any desired mixing ratios.

[0111] Polyamide molding compounds are prepared in a manner known per se, which involves mixing the components in the appropriate weight proportions.

[0112] It is also possible to use recyclates of the individual components or else mixtures, in particular mixtures of components A) and B. Through the addition of component C), such recyclates may be converted into molding compositions according to the invention.

[0113] The mixing of the components is preferably carried out at elevated temperature by commixing, blending, kneading, extruding or rolling. The temperature during mixing is preferably in the range of 220° C. to 340° C., particularly preferably in the range of 240° C. to 320° C. and in particular in the range of 250° C. to 300° C. Suitable methods are known to those skilled in the art.

[0114] Molded products (molded products) The invention further relates to moldings produced using the polyamide molding composition according to the invention.

[0115] The polyamide molding compounds can be used to produce moldings by any desired suitable processing technique, in particular injection molding, extrusion, coextrusion, thermoforming or any other polymer forming method. These and further examples can be found, for example, in "Einfaerben von Kunstrstoffen" [Coloring of Plastics], VDI-Verlag, ISBN 3-18-404014-3.

[0116] The invention also relates to a method for producing the molding material according to the invention, which comprises mixing components A), B), C) and optionally D) in suitable amounts, preferably by extrusion. This method may use commercially available twin-screw extruders of various sizes (screw diameters). The temperature during extrusion is 200°C to 400°C, preferably 250°C to 350°C, particularly preferably 250°C to 320°C.

[0117] The moulded articles produced from the moulding material according to the invention are used for producing internal and external parts, which are preferably load-bearing or have a mechanical function and which are from the sectors of electrical, furniture, sports, mechanical engineering, hygiene and health, pharmaceuticals, energy technology and drivetrain technology, vehicles and other transport means, casting materials for telecommunication devices and equipment, household appliances, household appliances, mechanical engineering, heating, fastening of equipment or of containers and all types of ventilation parts.

[0118] The mechanical properties, especially the impact strength, of the moulded bodies according to the invention are outstandingly high, which is combined with improved shrinkage.

[0119] Treatment Method Useful processing methods are the usual processing methods, e.g. extrusion, injection molding but also: - CoBi injection or assembly injection molding for hybrid components, in which the polyester molding materials according to the invention are combined with other compatible or incompatible materials, such as thermoplastics, thermosets or elastomers; - insert components, such as bearing seats or screw thread inserts, made of the molding material according to the invention and overcoated with other compatible or incompatible materials, such as thermoplastics, thermosets or elastomers; - outsert components, such as frames, casings or supports, made of the molding material according to the invention and into which other compatible or incompatible materials, such as thermoplastics, thermosets or elastomers, are injected; - hybrid components (elements made of the molding materials according to the invention in combination with other compatible or incompatible materials, such as thermoplastics, thermosets or elastomers), produced by composite injection moulding, injection welding, assembly injection moulding, ultrasonic welding, friction welding or laser welding, bonding, beading or riveting; - semi-finished products and profiles (e.g. produced by extrusion, pultrusion or lamination); surface coatings, laminations, chemical or physical metallization, flocking, in which the polyamide moulding composition according to the invention may be the substrate itself or the substrate support or, in the case of hybrid / bi-injection components, a defined substrate region, which can be brought to the surface by subsequent chemical (e.g. etching) or physical (e.g. mechanical or laser ablation) treatments; -Printing, transfer printing, 3D printing, laser marking Also includes.

[0120] The following examples are illustrative of the present invention without, however, limiting it in any way. EXAMPLES

[0121] [Table 1]

[0122] [Table 2]

[0123] [Table 2]

Claims

1. 1. A method for increasing the impact strength and / or elongation at break of molded articles made of a molding material comprising a thermoplastic polyamide and an elastomer, comprising using glass fibers having a tensile strength according to DINISO 527-5 of 86.0 to 92.0 GPa, a tensile modulus according to DINISO 527-5 of 2600 to 3200 MPa and a softening point according to DINISO 7884-1 of 900°C to 950°C, C1) 55.5% to 62.0% by weight of SiO 2 , C2) 14.0% to 18.0% by weight of Al 2 O 3 , C3) 11.0% to 16.0% by weight of CaO; C4) 6.0% to 10.0% by weight of MgO; C5) 0% to 4.0% by weight of further oxides; A glass fiber having the composition: C3) CaO and C4) MgO have a total ratio in the range of 17.0 to 24.0 mass%, and the total mass percentage of C1) to C5) is 100 mass%, C5) The process, characterized in that the further oxide is an oxide of the elements Zn, Mn, V, Ti, Be, Sn, Ba, Zr, Sr, Fe, B, Na, K or mixtures thereof.

2. The thermoplastic molding material is b1) As component B1), ethylene and 3~12 -Olefin, C 1~12 - copolymers with at least one comonomer selected from alkyl (meth)acrylates, (meth)acrylic acid and maleic anhydride, b2) as component B2), polyethylene or polypropylene, and 2. The process according to claim 1, wherein components B1) and B2) may additionally be grafted with maleic anhydride.

3. a) 30.0% to 89.0% by weight of at least one thermoplastic polyamide as component A), b) 1.0% to 30.0% by weight of at least one elastomer as component B), b1) As component B1), ethylene and 3~12 -Olefin, C 1~12 - copolymers with at least one comonomer selected from alkyl (meth)acrylates, (meth)acrylic acid and maleic anhydride, b2) as component B2), polyethylene or polypropylene, at least one elastomer, which may additionally be grafted with maleic anhydride, c) as component C) 10.0% to 69.0% by weight of glass fibers, which have a tensile strength according to DINISO 527-5 of 86.0 to 92.0 GPa, a tensile modulus according to DINISO 527-5 of 2600 to 3200 MPa and a softening point according to DINISO 7884-1 of 900° C. to 950° C., d) 0% to 30.0% by weight of further additives and processing aids as component D), and the total mass percentage of components A) to D) is 100% by mass, C1) 55.5% to 62.0% by weight of SiO 2 , C2) 14.0% to 18.0% by weight of Al 2 O 3 , C3) 11.0% to 16.0% by weight of CaO; C4) 6.0% to 10.0% by weight of MgO; C5) 0% to 4.0% by weight of further oxides; A component C) having the composition C3) the total proportion of CaO and C4) MgO is in the range of 17.0 to 24.0 mass%, and the total mass percentage of C1) to C5) is 100 mass%, C5) Thermoplastic molding compositions, characterized in that the further oxides are oxides of the elements Zn, Mn, V, Ti, Be, Sn, Ba, Zr, Sr, Fe, B, Na, K or mixtures thereof.

4. 4. The molding material according to claim 3, characterized in that component D) comprises a heat stabilizer, carbon black, and a lubricant.

5. 5. The molding material according to claim 3, wherein component B) is used in an amount of from 2.0% to 20.0% by weight.

6. 6. The molding material according to claim 3, wherein component A) is selected from the group consisting of polyamide 6, polyamide 66, polyamide 6.10 and copolymers or mixtures thereof.

7. 7. The molding material according to claim 3, wherein component C) is used in an amount of 10.0% to 55.0% by weight.

8. At least one comonomer is 3~8 -Olefin, C 2~6 8. The molding material according to claim 3, further comprising a component B1) selected from the group consisting of alkyl acrylates, maleic anhydride.

9. 9. The molding material according to claim 3, further comprising components B1) and / or B2) grafted with maleic anhydride.

10. 10. A process for producing the thermoplastic molding material according to claim 3, by mixing components A) to C) and optionally D).

11. Use of the thermoplastic molding material according to any one of claims 3 to 9 for producing fibres, films and moulded articles.

12. A fiber, film or molded article made from the thermoplastic molding material according to any one of claims 3 to 9.

13. A method for producing a fiber, film or molded article according to claim 12 by extrusion, injection molding or blow molding of a thermoplastic molding material according to any one of claims 3 to 9.

Citation Information

Patent Citations

  • Polyamide moulding material and its application

    EP2703436A1

  • Enodeb and UE for dynamic cell on and off

    EP3120663A1

  • Automotive pedal made of polyamide

    JP1985049035A

  • Polyamide blow molding

    JP1992288341A

  • Long-fiber-reinforced polyolefin resin structure and its molded product

    JP1994192448A